Knowledge Relationship About Lactation Management With Maternal Behavior In Breastfeeding - Hasliah; A.Nurlaela Amin; Fitriani (Jurnal Life Birth, 2021)
The background of this study is that breastfeeding behavior is an active act of a mother in exclusive breastfeeding that is without additional food from the baby born to 6 months of age. The purpose of the research is the known relationship of maternal knowledge about lactation management with maternal behavior in breastfeeding at the Puskesmas Kajang Kecematan Kajang Bulukumba Regency. The research method conducted is descriptive correlation research with a Cross-Sectional approach. Data collection using questionnaires. The number of respondents to 47 mothers had babies 6-12 months with simple random sampling technique. The results showed that using the chi-square statistical test obtained a value of Ï = 0.028< Î± = 0.05. Then there is a difference in proportion between maternal knowledge of lactation management and maternal behavior in breastfeeding or other words. There is a relationship between maternal knowledge of lactation management and maternal behavior in breastfeeding. Conclusion and Advice are that there is a knowledge relationship about lactation management with maternal behavior in breastfeeding in public Health Kajang districts kajang Bulukumba regency. The research results can add science and can be used as additional libraries in the field of science for educational institutions Stikes Panrita Husada Bulukumba.